Problematizing capitalism(s): Big difference? - Peck, Jamie (Environment & Planning A, 2019)
In the article, the author examines the social science theories of Fred Block, particularly on such topics as capitalism, finance, markets, and government. Other topics include Block's opinions on Polanyian socioeconomics, his thoughts on economic diversity and capitalist transformation, as well as the universalist model of capitalism as free-market globalism.
Keywords: BLOCK, Fred L.; capitalism; finance; free enterprise; markets; social sciences; the state

Can Karl Polanyi Explain the Anthropocene? The Commodification of Nature and the Great Acceleration - Steinberg, Ted (Geographical Review, 2019)
The most important historical work on the Anthropocene to date is J. R. McNeill and Peter Engelke’s The Great Acceleration: An Environmental History of the Anthropocene since 1945 (2016). The authors argue that the Anthropocene began in 1945, not in the eighteenth century, as some scientists have proposed. They single out unintentional “human actions” as the driving force behind the significant changes in biogeochemical processes unfolding since the middle of the twentieth century (McNeill and Engelke 2016, 4, 208). The main title of their book mimics a phrase first used at a 2005 conference on the future of the planet and refers to the escalating human threats to the so-called Earth System. The title was meant to parallel Karl Polanyi’s The Great Transformation: The Political and Economic Origins of Our Time (1944). Born in 1886 in Hungary, Polanyi became one of the world’s greatest economic historians. In an endnote to their book, McNeill and Engelke explain that Polanyi saw the “market economy” as a recent invention that “must be understood as embedded in social traditions, customs, and habits of the mind.” Likewise, they continue, human impacts on global ecology “are embedded in societies and their traditions” (McNeill and Engelke 2016, 213).
Keywords: ENGELKE, Peter; Great Acceleration: An Environmental History of the Anthropocene Since 1945, The (Book); MCNEILL, J. R.; anthropocene epoch; capitalism; globalization; nonfiction; urban development

Postneoliberalism as institutional recalibration: Reading Polanyi through Argentina’s soy boom - Berndt, Christian; Werner, Marion; Fernández, Víctor Ramiro (Environment and Planning A: Economy and Space, 2019)
While postneoliberalism is often interpreted as a societal reaction against the deleterious effects of marketization in Latin America, this paper develops a finer-grained Polanyian institutional analysis to gain better analytical purchase on the ambivalent outcomes of postneoliberal reforms. Drawing on recent insights in economic geography, and in dialogue with the Latin American structuralist tradition, we elaborate our framework through a case study of the Argentinian soy boom of the 2000s, identifying forms of market extension, redistribution, reciprocity and householding that facilitated this process. We argue for a multi-scalar approach that balances attention to national and extra-local dynamics shaping the combination of these forms, identified through the lens of the “fictitious commodities” of the soy boom: money (credit, currency and cross-border capital flows), land (in the agricultural heartland and frontier regions), labor (transformed and excluded in a “farming without farmers” model) and, we add, knowledge (biotech). Our analysis identifies internal tensions as well as overt resistance and “overflow” that ultimately led to the collapse of postneoliberal regulation of the soy complex, ushering in a wider, market-radical counter-movement. Refracting double-movement-type dynamics through the prism of heterodox institutional forms, we argue, allows for a better grasp of processes that underlie institutional recalibrations of progressive and regressive kinds.
Keywords: Argentina; Polanyi; institutions; marketization; post-neoliberalism; soy; uneven development

Between perfection and damnation: The emerging geography of markets - Cohen, Dan (Progress in Human Geography, 2018)
Economic geographers have recently taken up the study of markets after a long period of inattention. This growing literature has highlighted the diverse spaces, scales, and fields where markets are present, as well as the ways in which markets vary in form. However, the study of markets in economic geography still exists in tension between neoclassical and Marxist conceptions of markets as predictable and approaches like the social studies of economization/marketization which emphasize their contingency. This paper argues that work of Polyani and Gramsci can provide a way forward for the subfield through conceptualizing markets as sites of social struggle.
Keywords: capitalism; counterhegemony; earth scientists; economic geography; economic systems; geographers; human geography; marketization; markets; neoliberalism

Karl Polanyi as a spatial theorist - Roberts, Philip (Globalizations, 2018)
The ‘spatial’ turn in political economy has re-invigorated Marxian analysis, allowing for new research programmes into urbanization, geopolitics, and social movement activity amongst other topics. This tendency emerged through a critical re-reading of Marx and Gramsci, amongst others, uncovering spatial analyses embedded in the logic of their arguments. Conversely, Karl Polanyi’s interlocutors have tended to add geographical analysis as an additional layer of theory, reading space ‘in’ to the text. However, a close reading reveals that a concern with space permeates Polanyi’s analysis. As such, it is possible to read space ‘out’ of Polanyi, adding a level of theoretical rigour and logical consistency when applying his insights to geographic topics. This article carries out an exegesis of Karl Polanyi’s work, uncovering a theoretical framework that deals with space, place, scale, fixity, and motion. From this vantage point, the article considers the potential implications of this new geographical reading of Polanyi.
Keywords: Marxist philosophy; POLANYI, Karl, 1886-1964; capitalism; geography; international political economy; neoliberalism; scale; social sciences; space; spatial turn

CONCEITOS DOS IRMÃOS POLANYI COMO FERRAMENTAS DE ANÁLISE DE INDICAÇÕES GEOGRÁFICAS: O CASO DA INDICAÇÃO DE PROCEDÊNCIA DO QUEIJO MINAS ARTESANAL DA REGIÃO DA CANASTRA/MG - Matos, Ligia Aparecida Inhan; Rovere, Renata Lèbre La (Revista Econômica do Nordeste, 2018)
O conhecimento e o território são estudados principalmente por duas ramificações teóricas: pelo enraizamento, baseado em Karl Polanyi e pelo conhecimento tácito, desenvolvido por Michael Polanyi. O objetivo desse artigo é, a partir de uma revisão das duas teorias, propor o uso delas como ferramenta de análise de indicações geográficas e aplicar esta análise ao caso da produção do Queijo Minas Artesanal.  A metodologia utilizada foi o levantamento bibliográfico primário e pesquisa de campo na região com produtores familiares, instituições endógenas e exógenas. Os resultados mostraram que para ocorrer a formalização é necessário que os produtores adquiram novos conhecimentos e inovações provenientes de instituições exógenas. Descobriu-se que as divergências de conhecimento se fundam, principalmente, na forma como o conhecimento tácito e o codificado são transmitidos. Entretanto, para assegurar o conhecimento tradicional do processo produtivo do Queijo Minas Artesanal será necessária a compreensão deste fenômeno por parte das instituições exógenas, que perpassa obrigatoriamente pela confiança e proximidade, somente percebida e transmitida pelas instituições endógenas. Assim a introdução de indicações geográficas pode desencorajar produtores tradicionais a continuar produzindo, levando a uma perda de conhecimento da região.
Keywords: Indicação Geográfica da Canastra.; POLANYI, Michael, 1891-1976; conhecimento tácito; instituições

Information Policy and the Spatial Constitution of Digital Geographic Information Markets - Alvarez León, Luis F. (Economic Geography, 2018)
Information policy has become one of the key instruments for the commodification and marketization of goods in contemporary capitalism. However, the spatializing role of this and other legal regimes has not been explored in depth. Among the categories of goods whose production and circulation is shaped by information policy, geographic information is increasingly salient in the digital economy due to the strategic and economic value derived from its integration of location and context. This article explores the role of information policy regimes in spatially bounding, structuring, and regulating digital geographic information markets. This is conducted through a Polanyian economic geographic approach that contextualizes, integrates, and synthesizes two types of geographic information market formations, and focuses on the institutional dimension of information policy regimes. In developing this approach, the article argues that legal regimes (in this case information policy) are capable of spatializing markets by structuring, integrating, and delimiting the actions of states and other actors, such as private corporations and consumers, within particular jurisdictions. The empirical section of the article illustrates this argument by showing how three aspects of information policy—(1) intellectual property, (2) infrastructure, and (3) commercialization—shape specific configurations of digital geographic information markets within the various administrative scales in the European Union, a globally influential jurisdiction for information policy, and where a regional digital market is in the process of construction. The article concludes by arguing that a Polanyian economic geographic approach provides a solid basis with ample versatility to account for the necessary integration of a legal perspective into the analysis of new kinds of goods (such as digital geographic information) and the spatialities of their emerging market configurations.
Keywords: United States; capitalism; digital economy; geographic information; geographic information systems; information markets; information policy; intellectual property; legal frameworks; prediction markets

Situated responses to the post‐political city: An introduction - Richter, Anna; Fitzpatrick, Susan (Area, 2018)
It seems with the ever more complex instituting of aggressive neoliberal renewal policies comes an intensified effort to use the language of consensus and civic unity. The post‐political debate frames this discussion, and it is from this perspective that we propose a fuller consideration of urban renewal policy, and how these forces are embedded within the narrowing of what has been called the “properly political”. In bringing together accounts of the dynamic political life of communities and groups of interest who are confronting urban renewal policy in Glasgow, we make a case for recognising an intensification of political articulation, position‐taking and action. This recognition comes in response to the argument that we are currently experiencing a post‐political consensus and that democracy has been annulled in the process. We see evidence of a Polanyian “double movement” in which the construction of consensual publics is such a marked characteristic across different accounts, and how this appears to have opened up new critical spaces of debate and action within the various communities of interest. We therefore openly question the post‐political as a condition, or a process, which seemingly unfolds unimpeded. We fear that “post‐political” runs the risk of becoming a citational practice, that through repetition of the term, a narrowing of political articulation and action within the debate starts to occur. Our case studies aim to highlight the blind spots of the post‐political debate by focusing on the actually existing spaces of political articulation and position‐taking apparent in Glasgow.
Keywords: Glasgow; articulation (speech); consensus (social sciences); debates & debating; political; urban policy; urban renewal

Pop-up Polanyi: Cultural entrepreneurs and the ‘vacancy fix’ - Scott, Michael; Szili, Gerti (City, Culture and Society, 2017)
Gentrification as an urban strategy pivots upon the dual mediation of the city as a site for aesthetic consumption and pleasure, and as a space of potential ground rent. The recent rise of urban regeneration programs that assist small scale cultural entrepreneurs into disused commercial property – ‘pop-up shops’ – is one example of the convergence of the urban cultural economy and gentrification. This article presents a preliminary explanation of the function of such urban programs through Karl Polanyi's socioeconomic concepts and the case of Renew Adelaide. It is argued that Renew aligns and then stabilises different Polanyian modes of economic integration (reciprocity, redistribution, and exchange), while inducing a partial and temporary de-commodification of urban space. This approach outlines how ‘pop-up’ programs contain multiple objectives. First, they induce the images of creative city vibrancy that can be folded into contemporary place marketing. Second, they enable celebrated entrepreneurial subjectivities to be performed. Third, they illustrate how ‘vacancy fixes’ are addressed via small-scale cultural projects supporting land banking for the owners of properties whose rent gaps have yet to be closed. This Polanyian approach explains how the modes of integration undergirding these programs are assembled via an orientation to the real or symbolic processes of gentrification.
Keywords: creative cities; cultural entrepreneurs; gentrification; modes of economic integration; pop-up; rent gap

Commodifying art, Chinese style: The making of China’s visual art market - Zhang, Jun (Environment & Planning A, 2017)
The economic value of art to cities and regions has recently been vigorously pursued and actively studied. The rapid ascendance of China as a superpower in the global art market and associated transformation of China’s art space, however, are yet poorly understood. This paper develops a Polanyian framework to interpret the spatial and institutional evolution of China’s art market, seeing the (de)commodification of art as a cumulative process embedded in geo-historical interplays of triple logics—cultural, capital, and political, unfolding within, and reshaping in turn, historically inherited spatial structures.
Keywords: China; Chinese art; art - economic aspects; art industry; art market; commodification; cultural and creative industries; public art spaces

Earth Incorporated: Centralization and Variegation in the Global Company Network - Haberly, Daniel; Wójcik, Dariusz (Economic Geography, 2017)
Over the past twenty years, a widening gulf has appeared between the increasingly internationalized financing arrangements of the world’s leading corporations and the persistence of nationally compartmentalized approaches to the study of corporate control. In lieu of direct empirical evidence on corporate control at the global level, the most widespread assumption is that the globalization of ownership has taken the form of an expansion of arm’s-length, market-based arrangements traditionally prevailing in the Anglo-American economies. Here, however, we challenge this assumption, both empirically and conceptually. Empirically, we show that three-quarters of the world’s 205 largest firms by sales are linked to a single global company network of concentrated (5 percent) ownership ties. This network has a hierarchically centralized organization, with a dominantglobal network coreof US fund managers ringed by a more geographically diversestate capitalist periphery. Conceptually, we argue that the this architecture can be broadly explained through a Polanyianvariegated capitalistmodel of contradictory market institutionalization, with the formation of the global company network actually a counterintuitive product of global financial marketization. In order to understand this process of network formation, however, it is necessary to extend Polanyi’s model of a double movement, mediated through political interventions in the market, to incorporate Veblenian processes of evolutionary institutional change, mediated through the market.
Keywords: asset management; asset management concentration; corporate ownership internationalization; evolutionary economic geography; evolutionary economics; financialization; global company network; globalization; sovereign wealth funds; state capitalism; stock ownership; variegated capitalism

Reproducing spaces of embeddedness through Islamic NGOs in Sub-Saharan Africa: reflections on the post-2015 development agenda - Tok, M. Evren; O’Bright, Ben (African Geographical Review, 2017)
This paper explores the nexus of religion, space, and development. It sheds light on the role of faith-based organizations (FBOs) as partners in sustainable development and key actors for achieving the Sustainable Development Goals in sub-Saharan Africa (SSA). Applying and building on the theoretical framework of Polanyi’sThe Great Transformationindicates that FBOs with value-laden agendas have formed new state spaces during the age of globalization, where state capacities are transferred to non-state actors at other levels. The case study of Qatari organizations in SSA demonstrates how their uptake of state capacities can lead to development efforts that are driven by faith apart from politics and economics, which help balance market liberalism and social protectionism to create the conditions for sustainable development. Among other things, FBOs offer alternative financing options and new opportunities for financial inclusion that are relevant to the implementation of the post-2015 development agenda.
Keywords: Africa; Qatar; development; economic development; embeddedness; faith based NGOs; faith based human services; state spaces; sustainable development

From supply management to agricultural subsidies—and back again? The U.S. Farm Bill & agrarian (in)viability - Graddy-Lovelace, Garrett; Diamond, Adam (Journal of Rural Studies, 2017)
Farm subsidies have become increasingly maligned in agricultural policy debates, but the merits of subsidies are a distraction from deeper political, economic, and ecological problems in agriculture. Drawing on a history of the U.S. Farm Bill, this paper argues that a fixation on farm subsidies ignores why they came into being, and more generally glosses over the imperative for modern states to intervene into agricultural economies. Karl Polanyi's 'double movement' framework is used to situate the rise and fall of agricultural supply management within food regime theory. In the second, or surplus food regime, the U.S. government wielded excess commodities as geopolitical tools—even as domestic farm policy labored to contain overproduction, and thus support agrarian viability. In the subsequent corporate food regime, “free market” agriculture displaces and discredits supply management, even as massive government intervention into how food is grown and sold continues. Making space to remember historical price support programs, to situate their accomplishments and limitations, and to recognize residual supply-management mechanisms (such as farm cooperatives and agricultural marketing orders) is crucial for fostering agricultural viability in the US and beyond. Twentieth century supply management had flaws, but it cannot be wholly omitted. This paper highlights key motivations, elements, and contradictions of these policies and programs to begin the process of considering how supply management principles and strategies could be updated and enhanced for 21st century agriculture. Such a framework would need to pay more attention to diversity within domestic and international agricultures, and be more sensitive to the multi-scalar dimensions of food systems.
Keywords: agricultural economics; agricultural subsidies; agriculture & state; business food service; food supply

Think tanks and the pressures for planning reform in England - Haughton, Graham; Allmendinger, Phil (Environment & Planning C: Government & Policy, 2016)
This article examines how advocacy think tanks have sought to influence the remaking of the English planning system. Pressure for planning reform has come particularly though not exclusively from the political right, which has sought to portray planning as a form of bureaucratic regulation, out of touch with the needs of modern, global economies and the needs of society. This research involved 27 interviewees, the majority of whom have worked in think tanks, whilst others worked in government or in advocacy and professional groups. We explore how despite years of critique and many reforms to the planning system, it is still portrayed as failing. Drawing on ideas around the experimental state, we seek to develop a better understanding of the dynamics behind the process of continuous calls for planning reform before turning to some of the implications for both planning and our understanding of how think tanks seek to influence policy.
Keywords: advocacy groups; environmental protection planning; experimental state; markets; planning reform; political reform; research institutes; think tanks

Toward a Polanyian network analysis: market and non-market forms of coordination in the rice economy of Vietnam - Prota, Laura (Journal of Economic Geography, 2016)
The study proposes a network-based methodology linking Polanyi's ideal types of coordination and deductive blockmodeling to identify different forms of coordination within an economy. Using the proposed methodology, the economy of rice in postsocialist Vietnam is interpreted as a double movement responding to market liberalization. Qualitative and relational data were collected from 323 households and firms in two communes of the Mekong River Delta of Vietnam. Results show that in one case markets and redistribution co-existed as competing forms of coordination, entailing different relations of production and labor conditions; while in the other they blended and constituted a hybrid house-holding system.
Keywords: Vietnam; Vietnam transition; blockmodeling; corporate governance; economic coordination; embeddedness; liberalization (finance); local governance; markets; networks; rice - economic aspects; social networks

Embeddedness and migrant tourism entrepreneurs: A Polanyian perspective - Su, Xiaobo; Chen, Zhigang (Environment and Planning A, 2016)
Tourism embodies flows of tourists, capital and information, as well as migration, including migrants who operate businesses. How do migrant entrepreneurs negotiate social ties and economic activities in their destinations? To answer this question, the paper draws on Polanyi’s work on embeddedness to explore migrant tourism entrepreneurs (MTEs) and their modes of integration in the practice of social and economic life. We argue that MTEs are situated in a complex matrix in which they must build economic connections with locals and government officials, yet maintain a respectful distance with local groups, and develop embedded ties with other fellow migrants and tourists. Embeddedness, juxtaposed with distance, indicates that in tourist destinations, mixed patterns of economic and social relations significantly influence MTEs’ social and economic life. A Polanyian perspective on embeddedness can provide useful theoretical tenets to understand entrepreneurial activities in a mobile world.
Keywords: Lijiang ancient town; embeddedness; migrant tourism entrepreneurs; social and economic life; tourism production system

The business of the Anthropocene? Substantivist and diverse economies perspectives on SME engagement in local low carbon transitions - North, Peter (Progress in Human Geography, 2016)
The involvement of private sector actors in low carbon urban transitions is a neglected element of geographical analysis. Drawing on Polanyian, cultural economic geographies and the non-capitalocentric ethics of JK Gibson-Graham’s diverse economies perspective, the paper engages with the wider literature on the engagement of small and medium enterprises (SMEs) in environmental action, corporate social responsibility and low carbon transitions to develop a substantivist account of the contribution of SMEs to local low carbon transitions. The paper argues that, contra formalist economic analyses of economic rationality, SME owners should not be thought of as uncritical profit maximizers but as actors in favour of positive low carbon futures. Thus the paper argues that Polanyian economic geographies and diverse economies perspectives, which rarely speak to each other, can be drawn together, and concludes with suggestions for future research.
Keywords: Polanyian geographies; carbon offsetting; cultrual geography; diverse economies; environmental protection; local business representation; local economic development; low carbon transitions; small business; social responsibility of business; substantivist

The New Washington Consensus: Millennial Philanthropy and the Making of Global Market Subjects - Mitchell, Katharyne; Sparke, Matthew (Antipode, 2016)
This paper outlines the emergence of a New Washington Consensus associated with leading philanthropies of the new millennium. This emergent development paradigm by no means represents a historic break with the market rationalities of neoliberalism, nor does it represent a radical departure from older models of early 20th century philanthropy. Rather, it is new in its global ambition to foster resilient market subjects for a globalized world; and new in its employment of micro-market transformations to compensate for macro-market failures. Focusing on reforms pioneered by the new philanthropic partnerships in education and global health, the paper indicates how the targets of intervention are identified as communities that have been failed by both governments and markets. The resulting interventions are commonly justified in terms of “return on investment”. But the problems they target keep returning because the underlying causes of failure are left unaddressed.
Keywords: development; education; global health; millennial philanthropy; neoliberalism; philanthropy; triple movement

For real: land as capital and commodity - Christophers, Brett (Transactions of the Institute of British Geographers, 2016)
With the aim of helping to revivify a stalled geographical literature on the place of land in capitalist political economies, this article presents a critique of the popular idea that land can be usefully conceptualised as a ‘fictitious’ form of capital or commodity. The critique is based primarily on a close and critical consideration of the grounds on which the identifiers and theorists of such fictitiousness – Marx/Harvey in the case of capital, Polanyi in the case of the commodity – distinguished it from ‘real’ variants. Those grounds, the article argues, are tenuous. And, far from disabling us, treating land as no more or less real than other forms of capital and commodity can empower us in productively revisiting and centring the question of land's political economy – a crucial undertaking in a world where the materiality of land to social relations is writ increasingly large.
Keywords: MARX, Karl, 1818-1883; capitalism; economic geography; fictitious capital; fictitious commodities; fictitious commodity; land; political economy; social economy

Polanyian Pathways: A review of The Power of Market Fundamentalism: Karl Polanyi’s Critique by Fred Block and Margaret R. Somers and For a New West: Essays, 1919–1958 by Karl Polanyi; edited by Giorgio Resta and Mariavittoria Catanzariti - Peck, Jamie (Economic Geography, 2016)
Keywords: BLOCK, Fred; CATANZARITI, Mariavittoria; For a New West: Essays 1919-1958 (Book); POLANYI, Karl, 1886-1964; RESTA, Giorgio; SOMERS, Margaret R.; The Power of Market Fundamentalism: Karl Polanyi's Critique, The (Book); book review; nonfiction

Countermovement, Neoliberal Platoon, or Re-Gifting Depot? Understanding Decommodification in US Food Banks - Lindenbaum, John (Antipode, 2016)
In this paper, I explore the decommodification that takes place in US food banks. I argue that food banks are neither Polanyian countermovements re-embedding the market in society nor tiny platoons of neoliberalism that advance market relations and state withdrawal. Rather, food banks are best understood as re-gifting depots that are part of the capital accumulation process. Recent scholarship on primitive accumulation, the disarticulations approach, and waste suggests that the devaluation of food products and the exclusion of human labor are everyday elements of capitalism. I conclude by examining the potential for progressive politics in US food banking.
Keywords: Polanyi - political & social views; Supplemental Nutrition Assistance Program (U.S.); United States Deptartment of Agriculture; commodification; decommodification; disarticulation; equality - social aspects; food banks; food security; primitive accumulation; re-gifting depot; waste

Organic farm volunteer tourism as social movement participation: a Polanyian political economy analysis of World Wide Opportunities on Organic Farms (WWOOF) in Hawai‘i - Mostafanezhad, Mary (Journal of Sustainable Tourism, 2016)
In recent years, Karl Polanyi's concept of the “double movement” has been resurrected to describe growing international resistance to neoliberal global capitalism. The double movement originally referred to counter-movements for social protection against the 19th and early 20th century laissez-faire market. Today, it describes the growth of new social movements which often resist neoliberal economic practices and ideologies. Drawing on Polanyi's concept of the double movement and on recent work on neoliberalism and new social movements, this article examines farm hosts' motivations for participation in World Wide Opportunities on Organic Farms (WWOOF). It argues that farm hosts tend to articulate their motivations as an attempt to proclaim solidarity with organic, spiritual, and educational new social movement agendas. It describes how a loosely articulated organic identity converges around three corollaryprotective counter-movements: organic food production and consumption, spirituality, and alternative education, exploring the creative ways people are resisting neoliberal capitalism at the intersection of alternative tourism and organic agriculture. Yet, despite hosts' intentions, the article illustrates how new social movement participation through WWOOF is in constant tension with the neoliberal agrarian and tourism marketplace in which it operates, as well as the perhaps unforeseen limits of its radical horizon.
Keywords: POLANYI, Karl, 1886-1964; agri-tourism; capitalism; critical theory; culture change; farm tourism; geography; neoliberalism; organic farming; sustainability; sustainable tourism; volunteer tourism

Ontario's infrastructure boom: a socioecological fix for air pollution, congestion, jobs, and profits - Nugent, James Patrick (Environment & Planning A, 2015)
Infrastructure projects provide a spatial fix by increasing the scale and rate of capital accumulation, and because infrastructure projects themselves absorb massive amounts of productive and finance capital. I seek to explain the timing, character, and consequences of a Can $85 billion infrastructure boom in Canada's largest province, Ontario, between 2003 until 2013. I focus on the expansion and privatization of environmentally oriented infrastructure in Ontario via three policies: the conversion of public coal power plants to private natural gas and nuclear facilities; the Green Energy Act (a renewable energy feed-in tariffs programme); and The Big Move (a Can $50 billion dollar rapid transit plan using a public–private partnership model). I employ a Polanyian– O'Connor approach to emphasize the role of labour, environmental groups, and other social movement groups in bringing these investments about. I argue that infrastructure investments are not only a spatial fix aimed at finding capital a safe long-term investment and addressing class struggles around job creation. In Ontario these infrastructure investments have also provided the state with a broader socioecological fix for the economic and political contradictions stemming from air pollution and congestion. Social movements have pressured the government to address what James O'Connor refers to as the underproduction of the conditions of production: that is, degraded human health and quality of life; a deteriorating environment; and inadequate public infrastructure. Throughout the paper I emphasize how the socioecological fix in Ontario is being accomplished by advancing the neoliberal governance of public infrastructure. I point to how these neoliberal socioecological fixes are simply displacing socioecological crises to new spatial and temporal scales.
Keywords: Canada; Ontario; Polanyian-O'Connor approach; air pollution; fictitious commodities; human ecology; infrastructure; infrastructure and the environment; neoliberal environmental fix; privatization; saving and investment; second contradiction of capitalism; social movements; socioecological fix; spatial fix

The political economy of orphanage tourism in Cambodia - Guiney, Tess; Mostafanezhad, Mary (Tourist Studies, 2015)
A recent Aljazeera report on ‘Cambodia’s Orphan Business’ explains ‘how “voluntourism” could be fuelling the exploitation of Cambodian children’. Anti-orphanage tourism movements have emerged to resist the growth of Cambodia’s contested orphanage tourism industry, which is blamed for widespread corruption and the exploitation of children for profit. Taking a Polanyian political economy approach, this article illustrates how the emergence of and response to the orphanage tourism industry represent, in Karl Polanyi’s words, a ‘double movement’ between the neoliberalization of orphanages and the corollary protective countermovement by anti-orphanage tourism campaigns that challenge the industry’s morality and legitimacy. It argues that while resistance to the commodification of orphanages under the newly neoliberalized Cambodian economy reflects Polanyi’s double movement thesis, the limits of this resistance are also indicative of how countermovements are challenged by the broader political economy in which they operate.
Keywords: Cambodia; double movement; hospitality, leisure, sport & tourism; orphanage tourism; tourism; tourist studies; volunteer tourism

Land as fictitious commodity: the continuing evolution of women's land rights in Uganda - Naybor, Deborah (Gender, Place & Culture: A Journal of Feminist Geography, 2015)
In sub-Saharan Africa, colonial influences have altered traditional practices as a way to manage that which Polanyi labeled as ‘fictitious commodities’ of land, labor, and money. Land has now become a highly marketable commodity and an intrinsic part of the global economy. Over the past century, Uganda's land rights have evolved from communal rights to that of male-dominated, individual ownership practices that have excluded women. Despite constitutional provisions, which confer title of both a deceased husband's property rights and equal rights to property within a marriage to a wife, postcolonial patriarchal tradition prevails. This article examines historical changes in land rights in Uganda and discusses the impact of shifts in land rights from communal ownership to individual tenure, altering power structures and attempting to create marketable land title. The Ugandan women's movement's opposition to policies and implementation of laws that exclude women has been unable to facilitate the required changes in unbiased access to land rights, despite apparent victories in revisions to the letter of the law. Situated within contemporary interpretations of tradition and pressures of market demand, this article shows that women's access to landownership and use are restricted by misinterpretation of traditional law and a lack of enforcement of contemporary legal rights. To illustrate the impact of a lack of access to land, this article examines an empirical case study of widowed subsistence farmers in southern Uganda. Women in Uganda continue to lose ground, quite literally, decreasing the possibility of gender equity in terms of land. (English)
Keywords: Uganda; derechos de las mujeres; free enterprise; gender; género; land; land tenure; legal status of widows; legal status of women; property rights; tierra; viuda; widow; women's rights; 乌干达; 土地; 女性权利; 寡妇; 性别

Les paiements pour services environnementaux de la Fondation Natura Bolivia entre logiques réciprocitaires, redistributives et marchandes, - Bétrisey, Florence; Mager, Christophe (Revue Française de Socio-Économie, 2015)
La diffusion internationale des paiements pour services environnementaux (PSE) a été interprétée en 2010 par le gouvernement bolivien d’Evo Morales comme une réponse strictement néolibérale à la nécessité d’assurer une gestion durable des ressources naturelles. Supposée amener à terme à l’éviction de toute régulation autre que marchande – qu’elle s’applique à la nature ou aux rapports entre personnes –, la mise en place de PSE n’a pas été encouragée par les autorités nationales boliviennes. Des projets de PSE ont toutefois été lancés, dont les Acuerdos Reciprocos por el Agua (ARA), issus d’un partenariat public-privé dans le département de Santa Cruz. En analysant leur conception et leur fonctionnement au prisme du référentiel polanyien, nous montrons que, contrairement aux craintes gouvernementales, ces PSE ne font pas abstraction des logiques organisationnelles réciprocitaires et redistributives, ajustant au contexte local un objet global., ENG: The international dissemination of payments for ecosystem services (PES) has been interpreted in 2010 by the Bolivian government of Evo Morales as a strictly neo-liberal response to the need to ensure a sustainable management of natural resources. Supposed to contribute to the crowding-out of any other regulation than market – applied to the nature or the relationship between people – the implementation of PES was not encouraged by the Bolivian national authorities. However some PES projects stemming from a public-private partnership have been initiated at local level, as the Acuerdos Reciprocos por el Agua (ARA), in the department of Santa Cruz. Analysing their design and operating through the Polanyian framework, we show that, contrary to the government fears, these PES do not ignore the reciprocal and redistributive organisational logics, adjusting a global object to the local context.
Keywords: Bolivia; Bolivie; Polanyi; hybridity; hybridité; logique marchande; market logic; paiements pour services environnementaux; payments for ecosystem services; reciprocity; redistribution; réciprocité; sustainable management

The New ‘Passive Revolution’ of the Green Economy and Growth Discourse: Maintaining the ‘Sustainable Development’ of Neoliberal Capitalism - Wanner, Thomas (New Political Economy, 2015)
This paper analyses the rapidly emerging discourse of a green economy based on green growth. It highlights inherent conflicts and contradictions of this discourse such as the myth of decoupling growth from the environment, pollution generations and resource consumption. Using key theoretical constructs of both Gramsci and Polanyi, the paper argues that the green economy/growth discourse can be seen as a Gramscian ‘passive revolution’ whereby the dominant sustainable development discourse, subsumed by capitalist hegemony, is protected in the context of global environmental, economic and development crises. The ‘neoliberalising of nature’, or in other words, the privatisation, marketisation and commodification of nature, akin to Polanyi's fictitious commodities, continues and intensifies with green economy/growth strategies. Greening the economy and associated strategies of green growth divert attention from the social and political dimensions of sustainability and issues of social and international justice. In this way, the inexorable march or ‘sustainable development’ of neoliberal capitalism is maintained. This paper goes on to argue that contesting the claims of green economy/growth discourse through political struggles by civil society against the neoliberalisation of nature is a sign of a slowly emerging counter-hegemonic ‘double movement’ which challenges capitalist hegemony and the commodification of society–nature relations.
Keywords: GRAMSCI, Antonio, 1891-1937; environmental economics; fictitious commodities; green economy; green growth; neoliberalising nature; neoliberalism; passive revolution; privatization; research; social justice - environmental aspects; sustainable development

Environmental protection as market pathology?: carbon trading and the dialectics of the 'double movement' - Carton, Wim (Environment & Planning D: Society & Space, 2014)
Polanyi's concept of the 'double movement' is frequently interpreted as the opposition between the problematic and unsustainable dynamics of the market and the benign and normatively desirable reaction against this by 'society'. This paper questions this dualistic interpretation of the double movement and undertakes a problematization of the Polanyian idea of social and environmental protection. It does this by revisiting the concept of the double movement in light of the recent proliferation of market-based mechanisms for environmental regulation. Through an exploration of the different interpretations of Polanyi's work, the paper presents a dialectical reading of the double movement that conceptualizes the idea of social protection within a broader capitalist framework. This is then illustrated with the case of emissions trading as a particular form of environmental protection. Carbon trading as a mitigation strategy, it is argued, corresponds to the Polanyian idea of 'social protection' in that its protective potential to reduce emissions is itself constrained by the socioeconomic framework within which it operates. This in turn points to the need for a critique of climate mitigation efforts that goes beyond a focus on current problems with emissions trading schemes.
Keywords: EU Emissions Trading Scheme; carbon offsetting; climate change; countermovement; emissions trading; environmental protection; pathology; socioeconomics

Spatial egalitarianism as a social ‘counter-movement’: on socio-economic reforms in Chongqing - Lim, Kean Fan (Economy & Society, 2014)
Through a framework drawn from Karl Polanyi's substantivist theorization of economic practices, this paper evaluates the quest for equitable urbanization in Chongqing, a major city-region in south-western China. Illuminating the tensions arising from two interrelated reforms, namely the ambitious attempt to construct 40 million m2of public rental housing between 2010 and 2012, and the large-scale drive to ensure peasant migrants enjoy equal access to social benefits as current urban residents, the paper explains how the quest for equitable urbanization magnifies two nationwide dimensions of institutionalized uneven development, namely (i) the caste-like categorization of populations according to ‘urban’ and ‘rural’; and (ii) the coastal bias in national economic development. The paper concludes that this state-driven pursuit of spatial egalitarianism in Chongqing expresses the dialecticism of economic development in China: it is a social ‘counter-movement’ against the effects of an uneven spatiality that was instituted to drive and deepen the marketization of Chinese society.
Keywords: China; Chongqing; double movement; economic reform; equality; hukou; public welfare; social change; spatial egalitarianism; state–market relations; substantivist; urban–rural integration

White Knights from the Gulf: Sovereign Wealth Fund Investment and the Evolution of German Industrial Finance - Haberly, Daniel (Economic Geography, 2014)
The period leading up to and following the global financial crisis has been characterized by rising global financial diversity and multipolarity, a process underscored by the growth of so-called sovereign wealth funds (SWFs). To date there has not been any systematic examination of the interactions between this rising global financial diversity and national economic institutional diversity. Here I apply an institutional 'comparative capitalisms' perspective to the analysis of Gulf Cooperation Council ( GCC) SWF investment in German industry since the onset of the global financial crisis. The evidence demonstrates that a growing number of German industrial firms-particularly the major automotive firms at the heart of German industry-have recruited long-term GCC SWF investment as an adaptive response to the stresses of financial restructuring, most importantly the appearance of hostile takeovers as a feature of the German corporate governance landscape. These patterns lend partial support to 'varieties of capitalism' ( VOC) arguments that institutional complementarity and comparative institutional advantage are likely to produce path dependent trajectories of national institutional evolution. They also lend partial support to critiques of VOC, emphasizing, on the one hand, the importance of the Polanyian 'double movement' of market expansion and containment and, on the other, the transnational foundations of national institutional diversity. I conclude that to fully explain these patterns, both VOC theories of institutional complementarity and comparative advantage, and Polanyian theories of the double movement, must be grounded in a 'generalized Darwinian' analysis of population-level selection dynamics.
Keywords: Germany; Gulf Cooperation Council; Polanyian double movement; capitalism; economic geography; financial globalization; foreign investments; generalized Darwinism; industries; liberalization (finance); sovereign wealth funds; variegated capitalism; varieties of capitalism

Urban poverty and regulation, new spaces and old: Japan and the US in comparison - Mahito Hayashi (Environment & Planning A, 2014)
After the 1970s the new urban poverty (NUP) ballooned in Japan and the US, and it evoked policy responses that produced new, rescaled regulatory spaces to contain the poor on the fringe of social rights and the capital circuit. The paper illuminates this process through the comparison of Japanese and US trajectories, both of which, evolving through economic crises, have established unique pathways. The author first constructs a theoretical framework based on Marxian, Polanyian, and Lefebvrean traditions. Then, he compares national-scale poverty regulation in Japan and the US from the 1950s through the 2000s. Lastly, the author examines how the countries' regulation of a major aspect of the NUP--homelessness--intensified multiscalar reseating processes. The paper concludes that regulation of the NUP represents a significant instance of uneven spatial development of capitalism mediated by the state that requires synthetic research.
Keywords: Japan; United States; capitalism; comparative studies; economic development; financial crises; financial crisis; ghettoization; homelessness; rescaling; the capital circuit; the new urban poverty; the regulation approach; uneven spatial development; urban poor

Marketisation, public services and the city: the potential for Polanyian counter movements - Warner, Mildred E.; Clifton, Judith (Cambridge Journal of Regions, Economy and Society, 2014)
Marketisation of urban service delivery gained renewed intensity in the crisis. Mobilising Polanyi’s concept of double movement, we analyse how marketisation of public services both creates and constrains the potential for urban counter movements in the USA and Europe. We identify three main urban responses: ‘hollowing out’, where cities engage in service cut backs; ‘riding the wave’, where cities attempt to harness the market; and ‘push backs’, where cities and citizen movements oppose marketisation. Although the city is constrained by marketisation at national and international levels, we find evidence of push back and, in it, the potential for public service alternatives.
Keywords: city; crisis; double movement; marketisation; public services; urban studies

Radical, reformist, and garden-variety neoliberal: coming to terms with urban agriculture's contradictions - McClintock, Nathan (Local Environment, 2014)
For many activists and scholars, urban agriculture in the Global North has become synonymous with sustainable food systems, standing in opposition to the dominant industrial agri-food system. At the same time, critical social scientists increasingly argue that urban agriculture programmes, by filling the void left by the “rolling back” of the social safety net, underwrite neoliberalisation. I argue that such contradictions are central to urban agriculture. Drawing on existing literature and fieldwork in Oakland, CA, I explain how urban agriculture arises from a protective counter-movement, while at the same time entrenching the neoliberal organisation of contemporary urban political economies through its entanglement with multiple processes of neoliberalisation. By focusing on one function or the other, however, rather than understanding such contradictions as internal and inherent, we risk undermining urban agriculture's transformative potential. Coming to terms with its internal contradictions can help activists, policy-makers and practitioners better position urban agriculture within coordinated efforts for structural change, one of many means to an end rather than an end unto itself.
Keywords: United States; agricultural sociology; alternative food networks; community gardens; food production; food security; neoliberalism; urban agriculture; urban farming; urban studies

Polanyi in the Pilbara - Peck, Jamie (Australian Geographer, 2013)
This paper outlines a ‘substantivist’ approach to the regional economy of the Pilbara in Western Australia, inspired by a constructive reinterpretation of Karl Polanyi's methodological legacy. Beyond the metaphor of embeddedness, it makes the case for a more wide-ranging methodological engagement with Polanyi's brand of substantivist socioeconomics, in dialogue with the empirical investigation of actually existing and variegated socioeconomic formations. A Polanyian optic, amongst other things, calls attention to enduring sources of heterogeneity in this distinctive regional-economic formation, even under the hegemonies extractive capitalism and neoliberal developmentalism.
Keywords: Aboriginal economies; economic geography; mining; the Pilbara

Turning Financial Markets inside Out: Polanyi, Performativity and Disembeddedness - Muellerleile, Chris (Environment and Planning A, 2013)
In light of the spread of markets across the globe and deeper into daily life, this paper argues for a more robust analysis and application of Karl Polanyi's conception of (dis)embedded markets coupled with the performativity thesis authored mainly by Michel Callon. It suggests that while disembeddedness as a concept is necessary for an analysis of contemporary financial markets that are increasingly self-referential, it is not sufficient. Despite the suggestion of a gulf between Polanyian and Callonian economics, there are important similarities in the two frameworks. The similarities are considered along with the considerable difference, all in an attempt to develop a more robust methodological framework for analyzing financial markets. Performativity, it is argued, can help fill the gaps in Polanyi's embeddedness framework, albeit only when that concept's tendency to produce aspatial and apolitical arguments are taken seriously. The paper uses an abbreviated case study of the development of US financial derivative markets in the 1970s and 1980s to argue that markets must be considered in light of both their institutional and geographic entanglements as well as their (dis)embeddedness in systems of calculativeness and mathematical modeling. Specifically the paper analyzes the tension between the derivative origin story authored by Donald MacKenzie, which focuses on neoclassical pricing models like the Black—Scholes—Merton option pricing formula, and my own empirical research, which suggests the urban-economic geography of Chicago played a key role in the development of these instruments.
Keywords: Black—Scholes; CALLON, Michel; Chicago; disembeddedness; economic geography; embeddedness; financial derivatives; markets; performativity; urban geography

Disembedding Polanyi: Exploring Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
The paper provides an introduction to a theme issue devoted to the influence—and the potential—of the work of Karl Polanyi in the field of economic geography. Polanyi has been an inspirational figure in the heterodox field of ‘socioeconomics’, where the inseparability of the economic and the social is taken to be axiomatic. He has also made recurrent appearances in economic geography since the early 1990s, as a progenitor of the ‘networks and embeddedness’ approach and in his role as a prescient critic of market fundamentalism. But the potential of Polanyian approaches in economic geography has only been fitfully explored. In this context, the contributions to this theme issue make the case for a more sustained—but also open, critical, and creative—engagement with Polanyi's legacy.
Keywords: economic geography; embeddedness

For Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
Karl Polanyi has been an influential but also somewhat elusive figure in economic geography. Best known for his evocative notion of social embeddedness, it is perhaps fitting that Polanyi's presence has been more metaphorical than substantive. The paper asks what a more engaged Polanyian economic geography might look like. Focusing on methodological affinities, a response is developed in terms of a commitment to the substantivist (as opposed to formal) analysis of actually existing economic formations, together with a more purposive embrace of institutionalism, holism, and comparativism.
Keywords: comparative economy; economic geography; institutionalism; substantivism

Living without Fruit Flies: Biosecuring Horticulture and its Markets - Phillips, Catherine (Environment and Planning A, 2013)
In this paper, informed by more-than-human and biosecurity literatures, I attend a neglected nonhuman considered a serious agricultural pest: the fruit fly. In addressing what it takes to live without fruit flies, biosecurity is theorised as ongoing, enacted achievement sustained (or not) by everyday and eventful interactions of heterogeneous spaces, strategies, and participants—human and nonhuman. Relations of fruits, flies, and people are explored through one vital attempt to biosecure life: Australia's Fruit Fly Exclusion Zone (FFEZ), a tristate pest-free area established to protect commercial horticulture from the fruit fly. Fruit flies become problematised as their appetites and mobilities confound fruit production and marketing, and affiliated biosecurity controls. Making fruit safe enrolls policy and agricultural sectors, but also more dispersed agents (travellers, residents, trees) and management sites (primarily off-farm). Since its introduction, the FFEZ's ongoing biosecuring normalised, with only occasional outbreak events. However, recent unprecedented outbreaks evoke questions about the FFEZ's future status. In such eventful times, it is worth reflecting on what kinds of living are possible in biosecurity zones—for flies, for resident human communities, and for agrifood networks.
Keywords: Australia; Queensland fruit fly; agriculture; biosecurity; more-than-human

Men and Things: Karl Polanyi, Primitive Accumulation, and Their Relevance to a Radical Green Political Economy - Prudham, Scott (Environment and Planning A, 2013)
Now is an important moment to be thinking and talking about a critical and normative green political economy. Whether via attempts to develop effective and socially just climate policies at multiple scales of governance [including REDD (reducing emissions from deforestation and degradation) schemes], or to develop proliferating and controversial neoliberal instruments for dealing with undesirable environmental change, environmental governance, and environmental change in the context of contemporary global capitalism are on the agenda. What would a critical and normative green political economy for the current moment look like? This paper draws on Karl Polanyi's The Great Transformation as a resource for answering that question. In particular, Polanyi's discussion of problematic and dualistic notions of nature and society in early political economy and the role he accords social struggles over land in developing his theory of fictitious commodities, embeddedness and the double movement are revisited. The paper stresses how Polanyi's ideas, at once conceptual and polemical, draw centrally on Marx's theorization of primitive accumulation as an inherent, ‘extra-economic’ facet of historical—geographical capitalism, a differentiated unity linking the commodification and objectification of human and nonhuman natures as exchange-values. In this respect, Polanyi offers (or seems to offer) a potential reconciliation of a politics of nonhuman and human nature through his emphasis on primitive accumulation as a site of both political struggle and epistemic transformation.
Keywords: Karl Polanyi; economism; green political economy; primitive accumulation

Institutional Mobility and Mutation in the Global Capitalist System: A Neo-Polanyian Analysis of a Transnational Cotton Standards War, 1870–1945 - Quark, Amy A. (Environment and Planning A, 2013)
This paper explores the dynamics of institutional change in periods of instability in the global capitalist system. Two recent bodies of literature—actor-centered institutionalism and the ‘policy mobilities’ approach—emphasize how contextual and historical specificities drive transformation as institutions move across space. However, scholars in both traditions give less attention to the systematic patterns of social conflict that influence how policies move and mutate. Drawing on the case of a standards war in the global cotton trade from 1870 to 1945, I build on these literatures by linking them to a neo-Polanyian theory of social conflict within periods of market-led development. From this view, we must understand institutions, their mobilities, and mutations as constituted by and constitutive of struggles over how the global capitalist system should be organized and in whose interests. This requires building on, but also deepening Polanyi's analysis. While Polanyi emphasized the destructive effects of liberal market projects that generate social conflict, the ‘push-backs’ against liberal market projects are more diverse than Polanyi suggested, and social conflict can also emerge out of the creative moments of liberal market expansion.
Keywords: cotton; double movement; history; interfirm competition; interstate competition; market expansion; standards

Marketization beyond Neoliberalization: A Neo-Polanyian Perspective on China's Transition to a Market Economy - Zhang, Jun (Environment and Planning A, 2013)
This paper proposes a neo-Polanyian framework of neoliberalization-as-marketization for understanding geohistorically embedded marketization based on five interlinked theoretical conceptualizations: embedded marketization, hybrid integration, double movement, active society, and qualitative state. I argue that this framework can be useful to supplement existing theorizing of neoliberalism, and to facilitate comparative case studies across vastly differently contexts. This framework is then taken to analyze China's post-Mao transition to a market economy. I argue that China's gradualist transition from a centrally planned economy to a mixed economy has been maneuvered by a self-regulating party-state (dis)embedded in a deactivated (active) society. Due to the existence of multiple veto players and intraparty ‘double movement’, the marketization was able to be mostly socially progressive until 1993. However, it was no longer the case when the ‘socialist market economy’ was enshrined and, without political liberalization, the Chinese version of neoliberalization has become even bleaker than elsewhere.
Keywords: China; double movement; marketization; neo-Polanyian; neoliberalization

The boundaries of cosmopolitanism: Karl Polanyi and the 'Magyar-Jewish mongrel' - Dale, Gareth (Environment & Planning A, 2013)
The author offers his opinion on Hungarian historian Karl Polanyi and the views Karl expressed in a series of letters he sent to his brother Michael Polanyi. In these letters Karl wrote about the Germans attitude towards other Jews and the developing volatile social environment in Budapest, Hungary at the beginning of the 20th Century. He also wrote on the animosity between the Germans and the Jews.
Keywords: Baltic States; Germans; Jews; POLANYI, Michael, 1891-1976; biography; cosmopolitanism; history; social development

Polanyian pedagogies in planning and economic geography - Rankin, Katharine N. (Environment & Planning A, 2013)
The author offers his opinion on social economic planning and the educational courses available on them. The author states that planning social economy was a part of Hungarian economist Karl Polanyi's policy in early 20th century to stabilize the economic conductions in Hungary at that time. The auditor says that Polanyi's book "the Great transformation" formed the basis. which if acted upon, would have preevented the Global Financial Crisis of 2008.
Keywords: Great Transformation, The (Book); POLANYI, Karl, 1886-1964; central economic planning; global financial crisis, 2008-2009; nonprofit sector

Class and situated knowledge in Polanyi's The Great Transformation - Schoenberger, Erica (Environment & Planning A, 2013)
The author offers his views on a controversial fundraising organized by then U.S. Presidential Candidate Mitt Romney in May 2012 where he commented that he won't be bothered about a section of society who only have access to national income but have not contributions or income tax to give. The author cites this as one the reason why Romney was not successful and states that Hungarian Economists Karl Polanyi's socioeconomics theory is relevant in the 21st century.
Keywords: Great Transformation, The (Book); POLANYI, Karl, 1886-1964; ROMNEY, Mitt, 1947-; income tax; national income; political fundraising; socioeconomics; voters

Polanyi, double movements, and political economic transformations - Smith, Adrian (Environment & Planning A, 2013)
The author offers his opinion on Hungarian Economist Karl Polanyi's opinion on social economy. The auth through use of recent events such as the Arab Uprising since 2011 and the post communism societies discusses Polanyi's views with those of political economic planners. The author states that social change within a society post the economic recession could have been avoided had Polanyi's views being taken seriously.
Keywords: Arab Spring Uprisings, 2011-; Arab countries; POLANYI, Karl, 1886-1964; double movement; history; nonprofit sector; political economic analysis; postcommunist societies; social change

The two Karls, or reflections on Karl Polanyi's The Great Transformation - Walker, Richard (Environment & Planning A, 2013)
The article reviews the book "The Great Transformation," by Karl Polanyi.
Keywords: Great Transformation, The (Book); book review; nonfiction; socioeconomics

A variety of capitalism … with Chinese characteristics? - Peck, Jamie; Zhang, Jun (Journal of Economic Geography, 2013)
The ‘varieties of capitalism’ framework represents an influential methodological innovation in the field of comparative political economy. It seeks to account for enduring spatial variations in national economic performance by recourse to macroinstitutional analysis, drawing ideal-type distinctions between liberal market economies, modeled on USA, and coordinated market economies, modeled on Germany. Moving beyond critiques of varieties literature—for instance, its methodological nationalism; its preoccupation with limited, formal registers of (national) institutional variety; its growing reliance on rational-choice, firm-centric methods; its failure to account for the pronounced interpenetration and mutual dependence of capitalist economies and its tendency to privilege typological elaboration over causal explanation—this article explores the critical (counter?) case of Chinese capitalism. It considers the extent to which the Chinese economy can be meaningfully characterized as capitalist; the character of its state form and recent development path and its position within—or beyond—conventional understandings of capitalist variety.
Keywords: China; Chinese capitalism; capitalism; developmental state; economic structure; economic systems; free enterprise; socialist state; variegated capitalism; varieties of capitalism

On Life as a Fictitious Commodity: Cities and the Biopolitics of Late Neoliberalism - Rossi, Ugo (International Journal of Urban & Regional Research, 2013)
Building on a biopolitical understanding of the economic crisis, this essay contends that the occurrence of the crisis warns that life is not a real commodity but - to put it in Karl Polanyi's terms - a 'fictitious commodity'. This means that life cannot be integrally subsumed within the economy, and therefore the crisis is to be seen as a pathological way in which societies react to the pervasiveness of capitalist relations, showing the illusory character of self-regulating markets and ownership ideologies. Two mutually contradictory biopolitical responses to the neoliberal crisis, led by the state and grassroots movements respectively, are discussed in the concluding section of the essay.
Keywords: biopolitics; biopolitics (sociobiology); capitalism; consumers; crisis; fictitious commodities; global financial crisis, 2008-2009; government regulation; home ownership; housing; late neoliberalism; neoliberalism; urban economics

Towards the Great Transformation: (5) Materialisms, old and new: theory, sources, and praxis (an introduction) - Catterall, Bob (City, 2013)
One of the major critical claims of this series is that the social and socio-spatial sciences, in their currently dominant form, cannot, for lack of a de-familiarising agenda, one that leads to an appropriate and continually tested strategy (praxis), effectively counter the normalized and naturalized forms and processes of late capitalist urbanization, normalized by mainstream theory in the service of established power, and their extrapolation into a ‘planetary future’. Critical urban theory presents/presented a step forward but it is losing some critical momentum and thus purchase on present and future realities in its neglect of aspects of its own intellectual heritage, of ‘extra-scientific’ resources including the cognitive aspect of the arts/humanities and ordinary experience (‘the university of the streets’), and in its too restrictive theoretical, spatial and temporal foundations.1 It thus, to a significant extent, fails to give an adequate account, a representational and ethical/normative accounting, of ‘the great transformation’ of marketisation/capitalism as told and analysed notably by Polanyi and Marx, and to the possibilities of and its relationship to praxis for a post-marketised/capitalist great transformation. We need a purposeful reading of the full range of the lived materialities of the planet (not just abstracted away into a distinctly immaterial usage of the notion of the ‘planetary’ and, indeed, of ‘urbanization’). We need in fact a sensuous materialism, an old but still unrealized project. This, the first of two futher episodes, is a brief retrospective and prospective survey, drawing on earlier work in this series and sketching in future directions, of such a materialism (materialisms, old and new): theory, sources and praxis.
Keywords: capitalism; cities & towns; cultural studies; de-familiarisation; marketisation; marketization; materialism; monsters; urban community development; urbanization

The ‘Double Movements’ of Neighbourhood Change: Gentrification and Public Policy in Harlem and Prenzlauer Berg - Bernt, Matthias (Urban Studies (Sage Publications, Ltd.), 2012)
This article explores the interrelation of gentrification and public policies in the neighbourhoods of Prenzlauer Berg (Berlin) and Harlem (New York City). It draws on Karl Polanyi’s concept of a ‘double movement’ and argues that gentrification is fundamentally a political process. Thus, while demise in the face of market forces, or even an active support of gentrification, is clearly visible in both neighbourhoods, the relation between public policies and gentrification is also highly unstable and contradictory. The cases studied highlight that the resources to push or prevent gentrification are contingent; they are not built into the essence of urban development.
Keywords: Berlin (Germany); Germany; Harlem (New York, N.Y.); economic conditions; gentrification; government policy; social conditions; urban planning; urban renewal

Neoliberalismo Crisis Actual - Peck, Jamie (Documentos y Aportes en Administración Pública y Gestión Estatal, 2012)
The article discuss the characteristic of the current neoliberalism to understand it as a changeable and complex project whose economic and political sustainability is continuously reinvented and whose governance and spatiality is in need of being understood differently, if a viable alternative is to be constructed. Taking the recent neoliberal crisis as a point of departure, it discusses three main and interrelated aspects: firstly, the polymorphic characteristics of neoliberalism as a process in transformation; secondly, the way in which it could be acted against this neoliberal process by bringing some contributions from Polanyi back into the analysis so as to understand neoliberalism's dynamics; thirdly, the characteristics of some current policies taking place under neoliberal process, some of which could became viable alternatives in the long term. (English)
Keywords: 21st century; POLANYI, Karl, 1886-1964; crisis; economic history; global financial crisis, 2008-2009; neoliberalism; neoliberalismo; political philosophy; political practices; practical politics; prácticas políticas; world politics - economic aspects

The point is to keep going: the global sub-prime mortgage crisis, local labour market repositioning, and the capital accumulation dynamic in Singapore - Lim, Kean Fan (Journal of Economic Geography, 2012)
The global subprime mortgage crisis in 2007–2008 led to an economic recession in Singapore, but the economy recovered strongly to post a 14.5% expansion in 2010. This article examines how labour market repositioning policies contributed to this recovery. Following Karl Polanyi's conceptualization of the economy as an ‘instituted process’, I explore how these policies function as state-driven redistributive strategies aimed at triggering reciprocal responses from employers and workers within the putatively self-regulatory local labour market. The Singapore case foregrounds the causal roles of place- and time-specific state–firm–labour interactions in precluding what Polanyi calls society's ‘double movement’ against market-driven regulation. This successful preclusion exemplifies how the conditions and relations of economic production are not reproduced solely through market exchange; to sustain the capital accumulation dynamic, complementary acts of reciprocity and redistribution from different socio-economic stakeholders could be equally, if not more, important.
Keywords: Singapore; capital accumulation dynamic; economic recovery; global financial crisis; instituted economy; labor market; local labour market; saving and investment; spatio-temporal variation; spatio–temporal fix

Territoire, innovation et développement durable : l'émergence d'un nouveau régime conventionnel? - Buclet, Nicolas (Revue d'Économie Régionale & urbaine, 2011)
ENG TITLE: Territory, innovation and sustainable development: towards a new conventional regime? ABSTRACT: The paper examines the increasing number of diverse local development initiatives around the world aiming to break away from the predominant economic system. These initiatives, we argue, despite a somewhat visible disparity, largely rest on relatively similar principles, values and references. We argue that they are effectively laying the foundation for a new conventional regime more attuned to sustainable development goals. The paper analyses the characteristics of this regime, which refuses market dominance and favours reciprocal exchanges, as defined by Karl Polanyi. It is, nevertheless, necessary to question the potential and limitations of this conventional regime. (English)
Keywords: Territoire; conventions; development economics; développement durable; economic development; economics; environment; innovation; mathematical models; sustainable development; territory

Toward a new countermovement: a framework for interpreting the contradictory interventions of migrant civil society organizations in urban labor markets - Martin, Nina (Environment & Planning A, 2011)
Low-wage migrant workers in the United States confront a perilous labor market, where wages are low, the risk of injury on the job is high, and the fear of apprehension by immigration authorities is widespread. There is increasing empirical evidence that civil society organizations are becoming involved in mediating labor-market problems, but work remains to be done in developing a robust theoretical conception of why such organizations are involved in this arena and how we might evaluate the impacts of their interventions. This paper presents a framework for interpreting the role of migrant civil society organizations as labor-market intermediaries, by extending Karl Polanyi's theory of the 'double movement' and more recent writing to neoliberalism and precarious work. On the basis of data collected from migrant nonprofit organizations in Chicago, I theorize migrant civil society organizations as part of the creation of a new countermovement that protects the interests of both workers and employers from the destructive nature of an unregulated labor market, as predicted by Polanyi. I catalogue organizations' responses to precarious work and create a generalizable framework for evaluating the contingent outcomes of their strategies. Organizations' work is interpreted as complex and sometimes contradictory: the potential to shield workers and advocate for progressive change is in constant tension with the neoliberal patterns of state and economic restructuring that such organizations can support.
Keywords: United States; civil society; immigrants; industrial mediation; labour market; migrant labor; migrant labour; neoliberalism; salaries, wages, etc.; societies, etc.

Nature, Capital and Neighborhoods: 'Dispossession without Accumulation'? - Kappeler, Aaron; Bigger, Patrick (Antipode, 2011)
The ongoing economic crisis, which originated in the USA and has since spread rapidly to capital markets worldwide, is massive, complex, and many times contradictory. One could say the same for responses to the crisis as governments, firms and multi-national institutions struggle to grasp the full magnitude of the event. This article interrogates the key commodities involved-land, labor and money-and the always-uneasy relations between spaces of social reproduction and capital. Such ambivalence is critical to understanding how new economic realities are formed in light of retreating neoliberalism as markets become destabilized. The analysis provided suggests the commodities involved in the housing crisis are the basis for a countermovement against dispossession.
Keywords: MARX, Karl, 1818-1883; United States; capital market; capitalism; housing market; international business enterprises; labor; labour; mixed economy; neoliberalism; social aspects

Food crises, food regimes and food movements: rumblings of reform or tides of transformation? - Holt Gimenez, Eric; Shattuck, Annie (Journal of Peasant Studies, 2011)
This article addresses the potential for food movements to bring about substantive changes to the current global food system. After describing the current corporate food regime, we apply Karl Polanyi's 'double-movement' thesis on capitalism to explain the regime's trends of neoliberalism and reform. Using the global food crisis as a point of departure, we introduce a comparative analytical framework for different political and social trends within the corporate food regime and global food movements, characterizing them as 'Neoliberal', 'Reformist', 'Progressive', and 'Radical', respectively, and describe each trend based on its discourse, model, and key actors, approach to the food crisis, and key documents. After a discussion of class, political permeability, and tensions within the food movements, we suggest that the current food crisis offers opportunities for strategic alliances between Progressive and Radical trends within the food movement. We conclude that while the food crisis has brought a retrenchment of neoliberalization and weak calls for reform, the worldwide growth of food movements directly and indirectly challenge the legitimacy and hegemony of the corporate food regime. Regime change will require sustained pressure from a strong global food movement, built on durable alliances between Progressive and Radical trends.
Keywords: corporate food regime; corporations; food movements; food prices; food security; food sovereignty; food supply; global food crisis; hunger; neoliberalism; peasant studies; right to food; social change; strategic alliances (business)

Neoliberalism and the Biophysical Environment 2: Theorising the Neoliberalisation of Nature - Castree, Noel (Geography Compass, 2010)
There now exists a significant body of theoretically informed empirical research into ‘neoliberal environments’. It comprises numerous studies which together explore the connections between neoliberal principles and policies, on the one side, and the biophysical world on the other. However, making sense of them is by no means straightforward, despite their common focus on neoliberal environments. It is currently left to readers of these studies to synthesise them into a wider, joined-up account of neoliberal environments. This and two companion articles aim for precisely this sort of broad and coherent understanding. The contribution of this second instalment is to present an overarching political economic theory of ‘neoliberal environments’. By synthesising concepts from the work of Karl Marx, Karl Polanyi and James O’Connor, this article presents a framework for thinking about how neoliberal policies relate to the biophysical world.
Keywords: MARX, Karl, 1818-1883; O'CONNOR, James; neoliberal environments

D/developments after the Meltdown - Hart, Gillian (Antipode, 2010)
Part of what makes the current conjuncture so extraordinary is the coincidence of the massive economic meltdown with the implosion of the neoconservative Project for a New American Century, and the reappearance of US liberal internationalism in the guise of “smart power” defined in terms of Diplomacy, Development, and Defence. This essay engages these challenges through a framework that distinguishes between “Development” as a post-war international project that emerged in the context of decolonization and the Cold War, and capitalist development as a dynamic and highly uneven process of creation and destruction. Closely attentive to what Gramsci calls “the relations of force at various levels”, my task in this essay is to suggest how the instabilities and constant redefinitions of official discourses and practices of Development since the 1940s shed light on the conditions in which we now find ourselves.
Keywords: GRAMSCI, Antonio, 1891-1937; US hegemony; United States; capitalism; capitalist crisis; development; economic development; essay (literary form); hegemony; militarism

Now and Then - Watts, Michael J. (Antipode, 2010)
Antipode was launched into the firmament of the 1970s. We might reflect upon how well the journal and its contributors fully appreciated the historical gravity and weight of what was surrounding the project to create “a radical journal of geography”. What sort of radicalism was on offer? The language was “social relevance” from “a radical (Left) political viewpoint”. In writing to celebrate Antipode's birthday, this time in another, and similar, firmament there is still the need to confront the challenge of radicalism and its meanings. Whether we agree with Perry Anderson that the last vestiges of the 1960s have been finally swept away, that the “fluent vision” of the Right has no equivalent on the Left and that embedded liberalism is now as remote as “Arian bishops”, where do radical alternatives stand in relation to the fractured hegemony of neoliberalism? At the very least the need for alternatives is more pressing than ever. David Harvey has proposed rethinking the idea of “the right to the city”. But what other rights might we rethink? I reflect upon this question by returning to the 1960s and 1970s and Marxist debates over the law, and by thinking about the possibilities offered by this Polanyian moment.
Keywords: ANDERSON, Perry; Magna Carta; Marxist philosophy; Polanyi moment; Polanyian moment; common law - history; commons; essay (literary form); law; law - political aspects; markets; radicalism; scholarly periodicals

Crisis, Continuity and Change: Neoliberalism, the Left and the Future of Capitalism - Castree, Noel (Antipode, 2010)
Abstract:  This essay's point of departure is the coincident economic and environmental “crises” of our time. I locate both in the dynamics of capital accumulation on a world-scale, drawing on the ideas of Marx, Karl Polanyi and James O’Connor. I ask whether the recent profusion of “crisis talk” in the public domain presents an opportunity for progressive new ideas to take hold now that “neoliberalism” has seemingly been de-legitimated. My answer is that a “post-neoliberal” future is probably a long way off. I make my case in two stages and at two geographical scales. First, I examine the British social formation as currently constituted and explain why even a leading neoliberal state is failing to reform its ways. Second, I then scale-up from the domestic level to international affairs. I examine cross-border emissions trading—arguably the policy tool for mitigating the very real prospects of significant climate change this century. The overall conclusion is this: even though the “first” and “second” contradictions of capital have manifested themselves together and at a global level, there are currently few prospects for systemic reform (never mind revolution) led by a new, twenty-first century “red-green” Left.
Keywords: Britain; European Union; climate change; economic crisis; emissions trading; environmental crisis; social formation

Is the Globalization Consensus Dead? - Wade, Robert (Antipode, 2010)
The development economist Dani Rodrik recently declared that “the globalization consensus is dead”. The claim has momentus implications, because this consensus has steered economic policy around the world for the past quarter century. It emanates from the heartland of neoclassical economics, and defines the central tasks of the Washington-based organizations which claim to speak for the world. This essay answers two main questions. First, is Rodrik's claim true, and by what measures of “consensus”? Second, to the extent that the consensus has substantially weakened, is the state returning to the heart of economic life, as Karl Polanyi might have predicted? The answers? First, the globalization consensus about desirable economic policy has weakened, though it is far from “dead”. Second, the western state is returning to the heart of economic life in response to the current global economic crisis, but will retreat soon after national economies recover—because unless the crisis becomes a second Great Depression, the norms of more free markets and more global economic integration will be politically challenged only at the margins. New rules of finance may be introduced, but with enough loopholes that by 2015 Wall Street and the City will operate in much the same way as in the recent pre-crisis past.
Keywords: Washington consensus; catch-up growth; financial crisis; globalization consensus; income distribution; pension funds; poverty

Fair Trade Banana Production in the Windward Islands: Local Survival and Global Resistance - Torgerson, Anna McLoughlin (Agriculture and Human Values, 2010)
Fair trade banana farming in the Windward Islands of the Caribbean has emerged since the late 1990s in response to a crisis. Rulings by the World Trade Organization ended a longstanding trade dispute between the US and the EU by eliminating a system of preferential access of Windward Island bananas to the UK market. What followed was a period of rapid decline in banana exports from these small islands and a widespread abandonment of banana cultivation. Those banana farmers who remain are now primarily fair trade producers. Fair trade banana production in the Windward Islands can thus be conceived as a survival strategy that farmers have developed in response to a particular instance of neoliberal globalization. The paper considers this response especially in the context of recent fieldwork on the island of St. Vincent. In light of contributions by several scholars who have drawn upon the work of Polanyi to understand both fair trade and resistance to neoliberalism, fair trade banana production in the Windward Islands appears significant not only as a local survival strategy, but also as part of a larger countermovement that resists neoliberal globalization.
Keywords: agriculture in international trade; economic development: agriculture; energy; environment; international trade organizations; micro analysis of farm firms, farm households, and farm input markets Q12; natural resources; other primary products; trade policy

No hay ganancia en la milpa: the agrarian question, food sovereignty, and the on-farm conservation of agrobiodiversity in the Guatemalan highlands - Isakson, S. Ryan (Journal of Peasant Studies, 2009)
Although they receive little recognition for their contribution, peasant farmers in the global South play a fundamental role in securing the long-term global food supply. Via their self-sufficient agricultural practices, they cultivate the crop genetic diversity that enables food crops to adapt to changing environmental conditions. In this paper I draw upon empirical data from the Guatemalan center of agricultural biodiversity to investigate the concern that market expansion will displace peasant agriculture and undermine a cornerstone of the global food supply. I find that even though peasants' livelihoods involve multiple forms of market provisioning, they also engage in a Polanyian 'double movement' to protect their subsistence-oriented agricultural practices from the potentially deleterious effects of markets. I also investigate the so-called 'agrarian question' about the effects of market expansion on the viability of peasant agriculture, finding that although new forms of market provisioning are likely exacerbating rural inequality, the income from market activities actually enables rural Guatemalans to reproduce the conditions for peasant agriculture. Ultimately, I observe that the conservation of agricultural biodiversity and, consequently, global food security are contingent upon the 'food sovereignty' of peasant farmers.
Keywords: Guatemala; agricultural biodiversity; agrobiodiversity; food crops; food industry; food sovereignty; food supply; globalization - social aspects; peasant differentiation; peasant livelihoods; peasant studies; peasants; right to food

Tall among the trees: Organizing against globalist forestry in rural British Columbia - Prudham, Scott (Journal of Rural Studies, 2008)
In January of 2001, the TimberWest Corporation permanently closed its Youbou sawmill facility near Duncan, British Columbia, Canada laying off 220 workers. On the surface, the Youbou mill closure reinforced a pervasive sense that workers and communities in the province are increasingly vulnerable to an ever more globally integrated and footloose forest industry. But a funny thing happened in Youbou; the workers fought back. While the mill was completely dismantled and scrapped, with no discernable response from the provincial government, workers from the Youbou sawmill banded together to form a new NGO called the Youbou TimberLess Society. Since its inception, the YTS has developed into one of the most unique and compelling voices for forest policy reform in BC. In so doing, the YTS also represents something of an anomaly in exhibiting many of the characteristics of so-called new social movements, and yet emerging from the industrial working class. This paper explores the ways in which the YTS has served as a powerful arena in which the subjectivities of sawmill workers and other community members have been transformed through organized resistance to global capital. At the same time, informed by the YTS, the paper draws on Polanyi's idea of the dual movement to examine scales and terms on which globalization and competing notions of autonomy are contested in moral economies of both work and nature. Copyright (c) 2008 Elsevier Ltd.
Keywords: Canada; activists; double movement; employees - Canada; forest policy; forest policy - Canada; forest products industry; forests and forestry; lumber industry - British Columbia; lumber industry - Canada; rural studies; social movements; social movements - Canada

In the Zone: Street Markets and Street Merchants in Socio-Legal Perspective - Morales, Alfonso (Conference Papers -- Law & Society, 2008)
Typically when we think of street markets we think of chaotic places full of energy and vibrating with danger and opportunity. Traders or governments create markets to meet existing and emergent demands as well as the unintended consequences of other policy decisions. It is this institutional design, this governance, this regulatory process that provides access to the market and organizes the vending space therein. Public and private entities operating in fiscally constrained environments should attend to the variety of ways there are to establish and regulate markets. Municipalities typically assume that a detailed management scheme is the best approach to managing access to markets and organizing the distribution of space, the assumption being that chaos would result in the absence of the state. However, this is not necessarily the case, merchants' can self-organize access to space as well as a stable and flexible spatial order, and this self-organization can minimize costs, improve access, and contribute to social goods and goals associated with having a public market.This article provides an empirical justification for this claim by examining the creation of Chicago's Maxwell Street Market (hereafter the Market), and describing the subsequent changes in the regulatory scheme of that Market. This discussion recalls Polanyi's observation that all markets are regulated, one way or another, but that the forms and character of regulation obviously varies -- and thus this article argues the thesis that even in apparently unregulated markets we will find regulation, self-created, that produces a social order, in this case a stable and flexible order that accommodates a variety of private and public circumstances and goals. Our case is Chicago's Maxwell St. Market, which between 1973 and 1994 resembled unfettered capitalism. An ethnically heterogeneous multitude of street entrepreneurs organized vending space with little violence in the absence of stable, state sponsored, legal expectations. But this self-organization is nested in an overall history of unregulated street commerce in the area, starting in the 1870s, followed by the City government's creation and regulation of the Market in 1912, then a period of regulation lasting 60 years, followed by a radical change in the regulatory regime that produced a self-organized Market for about 20 years, then finally the City recaptured the Market and has regulated it again since 1994. Planners and policy makers will find this case interesting for three reasons: first, it is an interesting history of public markets and planning interests, second, the data indicate how an ethnically heterogeneous population can self-produce a flexible and stable social order and third, planners and policy makers concerned with locally appropriate and economically efficient, combinations of government and self-regulation of economic activities might apply lessons from this case to the large and growing interest in public markets around the country. ..PAT.-Unpublished Manuscript
Keywords: government regulation; markets; municipal government; nation-state; policy sciences

The Polanyian Way? Voluntary Food Labels as Neoliberal Governance - Guthman, Julie (Antipode, 2007)
Voluntary food labels that express ecological, social, and/or place-based values have been posed as an important form of resistance to neoliberalization in the Polanyian sense of protecting land, other natural resources, and labor from the ravages of the market. At the same time, these labels are in some respects analogs to the very things they are purported to resist, namely property rights that allow these ascribed commodities to be traded in a global market. After reviewing the Polanyian claims about these labels, the paper examines how these labels are operationalized and notes important differences in the sort of barriers to entry they erect, which in turn have quite different distributional consequences. It then goes on to discuss how these labels look to be an expression of roll-out neoliberalization. Following Heynen and Robbins who note four dominant aspects of neoliberalization of environmental governance (governance, privatization, enclosure, and valuation), to which a fifth (devolution) is added, the paper shows how these labels not only concede the market as the locus of regulation, but in keeping with neoliberalism's fetish of market mechanisms, they employ tools designed to create markets where none previously existed. In recognition that neoliberal political economies and subjectivities have delimited the possible, the paper also grapples with how these labels may produce political openings outside of their most proximate effects.
Keywords: agro-food governance; community studies; depletion allowances; fair trade; food labeling; government ownership; labeling; liberalism; natural resources; neoliberalism; organic food; privatization

Fighting standards with standards: harmonization, rents, and social accountability in certified agrofood networks - Mutersbaugh, Tad (Environment & Planning A, 2005)
In this paper I explore the remaking of globalized standards through harmonization, and its impact upon certified-organic and fair-trade agrofood networks. I focus on certification standards and discuss four shifts associated with globalized standards (an increased importance of multilateral institutions, changes to standards language, displacement of network-specific standards, and a shift away from relational standards). It is then argued, with reference to value-chain rent theory, that the shift to globalized standards has transformed rent relations in ways that benefit certain actors (that is, retailers) and imperil the earnings of others. In brief, globalized standards increase the costs of standards compliance, the full burden of which falls upon immiserated producers, to the point at which farmers see little economic advantage to certified-organic and fair-trade production. I then examine social-accountability standards that seek to `fight standards with standards' by championing the consolidation of strong labor and environmental protections under a single label. The study suggests that a single-label strategy can be successful, yet must struggle to overcome a Polanyian double bind, for, in order to build broad coalitions necessary to extend the reach of protective standards, the coalitions must include corporate interests that prefer weaker, contract-based standards.
Keywords: agricultural accounting; agricultural industries; applied ecology; environmental policy; retail industry; retail stores

Gramsci, Polanyi and Impressions from Africa on the Social Forum Phenomenon - Bond, Patrick (International Journal of Urban and Regional Research, 2005)
The  rise  of  the  Social  Forum  phenomenon  has  been  heartily  welcomed,  partly  so  as to unite diverse discourses of anti-neoliberal and anti-imperialist resistance under a common  banner.  There  are  debates  worth  flagging,  however,  that  draw  our  attention to  political  philosophies  (typically  binary  statist  versus  anti-statist  disputes),  visions of agency (typically networked movements versus parties), and potentials for revolutionary processes to emerge within ‘civil society’. In the spirit of Polanyi, many South Africans and other Africans are working on ‘decommodification’ strategies that range from particular sites of project-level struggles to national, regional and international advocacy. But we must be conscious, as well, of warnings by Gramsci about the long march through a civil society often co-opted to support state and neoliberal projects. The merits of African intellectual engagements with radical social movements have been shown in sites such as South African cities, but the African Social Forum awaits further opportunities to welcome allied researchers and academics. As the World Social Forum comes to Africa in 2007, Marcuse’s hope that the constituent movements begin to coalesce around a program is timely. However, this is likely to emanate more from intra-sectoral networks rather than from multidisciplinary moments such as the WSF itself. La montée du phénomène des Forums sociaux a été accueillie chaleureusement, en partie comme manière d’unifier sous un même drapeau les multiples discours de la résistance anti-néolibérale et anti-impérialiste. Certains débats éminents attirent pourtant l’attention sur des philosophies politiques (généralement des oppositions binaires étatistes/anti-étatistes), des visions de l’intermédiation (en général, mouvements interconnectés/partis) et des processus révolutionnaires susceptibles de naître au sein de ‘la société civile’. Dans l’esprit de Polanyi, nombre d’Africains, du Sud et d’ailleurs, s’emploient à des stratégies de ‘démarchandisation’ couvrant à la fois sites de conflit particuliers liés à un projet et plaidoyers aux niveaux national, régional et international. Toutefois, il ne faut pas oublier les avertissements de Gramsci pour qui la longue marche passant par la société civile risquait d’être cooptée afin de soutenir des projets gouvernementaux ou néolibéraux. Si les engagements d’intellectuels africains aux côtés de mouvement sociaux radiaux se sont révélés bénéfiques dans des cas tels que les villes d’Afrique du Sud, le Forum social africain espère d’autres occasions de rallier chercheurs et universitaires. Comme le Forum social mondial se tiendra en Afrique en 2007, l’espoir de Marcuse — de voir les mouvements constitutifs s’unir progressivement autour d’un programme — est d’actualité. Cependant, cette évolution viendra plus probablement de réseaux intra-sectoriels que d’élans multidisciplinaires comme le FSM.
Keywords: GRAMSCI, Antonio, 1891-1937; South Africa; decommodification; development studies; geography; social forum phenomenon

The Continuing 'Wind of Change' in the Balkans: Sources of Housing Inequality in Bulgaria - Vesselinov, Elena (Urban Studies (Routledge), 2004)
The research in this paper explores the institutional changes in the housing system during the period of market transition in Bulgaria, which follow suit with the greater societal transformations. The societal changes are linked theoretically with Polanyi's understanding of the transition from a non-market to a market society. His argument helps in establishing the institutional context of the macroeconomic changes in the past decade. The article then focuses on the changing sources of housing inequality. It is argued that there are two urban regimes of housing inequality: the regime of controlled uniformity during the period of socialism and the regime of primitive diversity during the period of market transition. The two regimes are produced mainly through the changing role of the state.
Keywords: Bulgaria; cities & towns; equality; housing; macroeconomics; socialism; urban studies

Rules of Privatization: Contradictions in Neoliberal Regulation of North Pacific Fisheries - Mansfield, Becky (Annals of the Association of American Geographers, 2004)
Recent changes in fisheries regulation in the U.S. North Pacific reveal how neoliberalism is constituted in practice, and the forms that neoliberalism takes when it engages with environmental management and ecological processes. Whereas neoliberalism can be taken as a political economic philosophy that posits that markets, without state involvement, can best allocate resources, the history and practice of neoliberalism show that it is not as unified as it often appears. Analysis of contemporary fisheries policy reveals not only contradictions in neoliberal approaches, but also how those contradictions are shaped by the environmental context of the industry. This article discusses the rationale for neoliberalism in fisheries and the governance changes enacted in the 1998 American Fisheries Act, which privatized the fishery for Alaska pollock by closing the fishery to all new entrants, providing a set percentage of the yearly catch to “cooperatives” of participants, and allowing individuals to lease their shares. Karl Polanyi's notion of the “double movement” provides a framework to argue that even though regulators tout these reforms because they rely on market mechanisms to resolve recalcitrant ecological and economic problems in these fisheries, writing and implementing the act simultaneously involved complex rule making designed to protect the market. This form of neoliberalism results from the history of fisheries regulation, including recent emphasis on cooperative management, and the ecological characteristics of marine fish. Moves to privatize the oceans entail developing distinctive forms of neoliberal practice that uniquely combine private industry and government regulation. Because fish are one of the last great resource commons, neoliberal approaches to fisheries mark a profound geographical transformation in the political economy of the oceans.
Keywords: Pacific Ocean; double movement; fishery policy; neoliberalism; privatization

'Spatial' relationships? Towards a reconceptualization of embeddedness - Hess, Martin (Progress in Human Geography, 2004)
The concept of embeddedness has gained much prominence in economic geography over the last decade, as much work has been done on the social and organizational foundations of economic activities and regional development. Unlike the original conceptualizations, however, embeddedness is mostly conceived of as a 'spatial' concept related to the local and regional levels of analysis. By revisiting the early literature on embeddedness - in particular the seminal work of Karl Polanyi and Mark Granovetter - and critically engaging with what I will call an 'overterritorialized' concept, a different view on the fundamental categories of embeddedness is proposed. This reconceptualization then is illustrated using the poststructuralist metaphor of a rhizome to interpret the notion of embeddedness and its applicability to different geographical scales.
Keywords: GRANOVETTER, Mark; associations; cosmography; economic geography; embeddedness; geography; global production networks; institutions; new regionalism; organization; rhizome; social networks; socioeconomics

The future of planning at the 'end of history' - Goonewardena, Kanishka (Planning Theory, 2003)
The hegemony of neoliberalism now poses a fundamental challenge to planners worldwide. Most influential in this regard has been Francis Fukuyama's 'end of history' ideology and its progenies - or mutations - such as the Third Way. A close reading of their proponents (especially Anthony Giddens) and critics (Perry Anderson, Pierre Bourdieu, Alex Callinicos, John Gray and others) with reference to the contrasting political-economic theories of Friedrich von Hayek and Karl Polanyi, however, reveals the fundamental contradictions of neoliberalism - especially between capitalism and democracy - and identifies for progressive planning the role of extending radical democracy to the realms of the state and the economy.
Keywords: BOURDIEU, Pierre, 1930-2002; FUKUYAMA, Francis; GIDDENS, Anthony; HABERMAS, Jurgen; neoliberalism; planning; social democracy

Ecosocialisation and environmental planning: a Polanyian approach - Low, Nicholas (Environment & Planning A, 2002)
Discusses a Polanyian approach to environmental planning, foregrounding the concept of ecosocialization. Global problems of urban modernity; Ecological modernization and the transformation of capitalism; Discussion on ecological Marxism and the transition to socialism; Polanyian perspective for environmental planning.
Keywords: capitalism; environmental engineering; human ecology

Planning and the Politics of Markets: Some Lessons from Financial Regulation in Nepal - Rankin, Katharine N. (International Planning Studies, 2001)
This paper calls for an explicit return to questions about the normative foundations of planning theory and practice. It argues that a simultaneous reading of Karl Polanyi with Friedrich von Hayek can contribute to developing an ethical basis for tempering market rationality with social rationality in the current global economic conjuncture. Empirically, the paper investigates recent initiatives in Nepal to provide social protections (à la Polanyi) through financial market rules. In the face of threats to the progressive legacy in planning practice posed by the prevailing neoliberal orthodoxy, Nepal's targeted lending policies and microcredit programmes offer some optimism about the potential to embed welfare provisions within market regulation, especially when compared to developments in other countries. At the same time, however, the perspectives of rural women explored here through critical ethnography raise key questions about the capacity of these regulations to generate social opportunity and highlight a role for locally situated social criticism in progressive planning practice.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Nepal; financial regulation; international planning studies; markets; planning; social protection

The Second Great Transformation: The Politics of Globalisation in the Global North - Zincone, Giovanna; Agnew, John (Space & Polity, 2000)
Dominant strands of thinking in contemporary social science consider economic globalisation, the increasing role of cross-border flows and transactions in economic organisation, in terms of some combination of either limited or considerable economic impact and either positive or negative consequences for the general welfare. Little attention has been given thus far to its political consequences within those parts of the world, the developed countries of the Global North, where its impact should be greatest. This paper argues that economic globalisation is in fact the geographical face of a new great transformation in the forces of production (reductions in transport and communication costs, dramatically increased capital and labour mobility, delocalisation of technological innovation, etc.) on a par in its potential impact with the transition to market society with fragmented states first identified by Karl Polanyi. Globalisation, it is claimed here, is the product of action by states as much as markets and, in the short-term, seems to accentuate social inequalities within states, to weaken the rights of current citizens, to lessen the weight of the democratic vote and to stimulate a profound restructuring of both work and the welfare state in the developed world or ‘Global North'. But more significantly, in the long term, when focus on globalisation shifts from its recent economic causes and short-term political impact to its more long term political consequences, recent trends towards a more global economy can be seen in a different light: as entailing a potential positive transformation in the geographical organisation of political rights and citizenship on a par with the first great transformation in economic life and citizenship signalled by the coming of market society.
Keywords: globalization; international economic relations; market society; political science; production (economic theory)

A Polanyi-inspired perspective on social-ecological transformations of cities - Bärnthaler, Richard; Novy, Andreas; Stadelmann, Basil (Journal of Urban Affairs, 2020)
Based on a Polanyi-inspired research program, we analyze urban transformations as interrelations between infrastructural configurations, i.e. context-dependent material infrastructures and their multi-scalar political-economic regulations, and socio-cultural modes of living. Describing different modes of infrastructure provisioning in Vienna between 1890 and today, we illustrate how political-economic processes of commodification and decommodification have co-evolved with socio-culturally specific modes of living, grounded in different classes and milieus. We show how, today, two modes of living—“traditional,” established during postwar welfare capitalism, and “liberal,” formed during neoliberal capitalism—co-exist. In the current conjuncture of rising inequality, neoliberal urban regeneration, and accelerating climate crisis, these modes of living are not only increasingly polarized and antagonistic, but also increasingly unable to satisfy needs and self-defined aspirations. Therefore, we explore the potential of social-ecological infrastructural configurations as an alliance-building project for a systemic social-ecological transformation, potentially linking different classes, social segments and forces around a common eco-social endeavor.

Re-grounding the city with Polanyi: From urban entrepreneurialism to entrepreneurial municipalism - Thompson, Matthew; Nowak, Vicky; Southern, Alan; Davies, Jackie; Furmedge, Peter (Environment and Planning A: Economy and Space, 2020)
Conventional approaches to local economic development are failing to address deepening polarisation both within and between city regions across advanced capitalist economies. At the same time, austerity urbanism, particularly in the UK, presents challenges for urban authorities facing reduced budgets to meet increased demands on public services. Municipalities are beginning to experiment with creative responses to these crises, such as taking more interventionist and entrepreneurial roles in developing local economies, generating alternative sources of revenue or financialising existing assets. Rooted in a Polanyian perspective and building on the concepts of the entrepreneurial state and grounded city, we identify an embryonic alternative approach – what we call ‘entrepreneurial municipalism’ – as a policy pathway towards resolving enduring socioeconomic problems where neoliberal urban-entrepreneurial strategies have failed. We situate entrepreneurial municipalism as one strand in an assemblage of new municipalist interventions, between radical urban social movements and more neoliberal strategies such as financialised municipal entrepreneurialism. Drawing on original research on the Liverpool City Region, we explore how local authorities are working with social enterprises to harness place-based assets in ways which de-commodify land, labour and capital and re-embed markets back into society. Finally, we draw upon Polanyi as our guide to disentangle differences in approach amongst divergent forms of municipalist statecraft and to critically evaluate entrepreneurial municipalism as a possible trajectory towards the grounded city.
Keywords: Entrepreneurial state; Polanyian economic geography; local economic development; municipal statecraft; urban policy